Exact renormalization group and [phi]-derivable approximations - Blaizot, Jean-Paul; Pawlowski, Jan M.; Reinosa, Urko (Physics letters, 2011)
We show that the so-called Φ-derivable approximations can be combined with the exact renormalization group to provide efficient non-perturbative approximation schemes. On the one hand, the Φ-derivable approximations allow for a simple truncation of the infinite hierarchy of the renormalization group flow equations. On the other hand, the flow equations turn the non-linear equations that derive from the Φ-derivable approximations into an initial value problem, offering new practical ways to solve these equations.